Correction : parole, prison, and the possibility of change - Austen, Ben (Flatiron Books, 2023)
"From the critically acclaimed author of High-risers comes a groundbreaking and honest investigation into the crisis of the American criminal justice system-through the lens of parole. Perfect for fans of Michelle Alexander's The New Jim Crow and Bryan Stevenson's Just Mercy The United States, alone, locks up a quarter of the world's incarcerated people. And yet apart from clichés-paying a debt to society; you do the crime, you do the time-there is little sense collectively in America what constitutes retribution or atonement. We don't actually know why we punish. Ben Austen's powerful exploration offers a behind-the-scenes look at the process of parole. Told through the portraits of two men imprisoned for murder, and the parole board that holds their freedom in the balance, Austen's unflinching storytelling forces us to reckon with some of the most profound questions underlying the country's values around crime and punishment. What must someone who commits a terrible act do to get a second chance? What does incarceration seek to accomplish? An illuminating work of narrative nonfiction, Correction challenges us to consider for ourselves why and who we punish-and how we might find a way out of an era of mass imprisonment"--